2022
DOI: 10.1097/prs.0000000000009098
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Matched Comparison of Health-Related Quality of Life in Bariatric Patients following Truncal Body Contouring

Abstract: Obesity is a worldwide epidemic associated with significant morbidity, early mortality, and substantial healthcare cost. [1][2][3] In the United States alone, the prevalence is more than one-third of the population. 4 Bariatric surgery is an effective treatment for obesity with overall mortality reductions cited at 30 percent. 5 Although successful bariatric surgery results in resolution or improvement in obesity-related comorbidities, this frequently comes at a patient-level cost-symptomatic excess and redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(52 reference statements)
2
4
0
Order By: Relevance
“…Prior research has primarily focused on the short-term effects of BS and BCS in cross-sectional or short-term prospective studies. 14,15,35,48 Our BS findings align with Kvalem et al, 49 where over 90% of participants were satisfied with the results 1-year post surgery, while only 69% were satisfied and felt that their expectations of BS were met 5 years post surgery. Similarly, other studies using the BODY-Q showed that HRQL for patients undergoing BS improved most significantly within the first year after surgery and then gradually declined.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Prior research has primarily focused on the short-term effects of BS and BCS in cross-sectional or short-term prospective studies. 14,15,35,48 Our BS findings align with Kvalem et al, 49 where over 90% of participants were satisfied with the results 1-year post surgery, while only 69% were satisfied and felt that their expectations of BS were met 5 years post surgery. Similarly, other studies using the BODY-Q showed that HRQL for patients undergoing BS improved most significantly within the first year after surgery and then gradually declined.…”
Section: Discussionsupporting
confidence: 87%
“…Prior research has primarily focused on the short-term effects of BS and BCS in cross-sectional or short-term prospective studies 14,15,35,48 . Our BS findings align with Kvalem et al, 49 where over 90% of participants were satisfied with the results 1-year post surgery, while only 69% were satisfied and felt that their expectations of BS were met 5 years post surgery.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…There is a misconception among healthcare providers and patients alike that BCS after MBS is an aesthetic intervention that suits only younger patients. On the contrary, the typical post-bariatric patient is a middle-aged female, who could potentially benefit further from BCS on the grounds of bariatric outcome, quality of life, and general well-being, as discussed in the Introduction [23]. Therefore, health-care providers, and especially bariatric surgeons, should encourage their patients to undergo BCS once their BMI has stabilized, provided they satisfy the established selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, plastic and reconstructive surgeons should assume a more proactive role when consulting in the context of the multi-disciplinary bariatric team. The second most common reason was inability to cover the costs or non-reimbursement by insurance companies to support this direction, which is a recognized issue worldwide [17,23]. Healthcare providers and policymakers should accumulate the evidence on the benefits of BCS for overall health, with the aim of adjusting the prevailing reimbursement policies.…”
Section: Discussionmentioning
confidence: 99%